Influencia das queimadas no comportamento das chuvas nos municipios de Botucatu e Piracicaba, estado de São Paulo - Lorenzo, Juan Manuel Fernández; Teramoto, Érico Tadao [UNESP]; Sánchez-Román, Rodrigo Máximo [UNESP]; González, Alba Maria Guadalupe Orellana [UNESP]; Escobedo, João Francisco [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2015)
This work used the time series of rainfall measured in the meteorological stations of FCA/UNESP-Botucatu (1971-2013) and of ESALQ/USP-Piracicaba (1980-2012), both located in São Paulo State, aims to verify the possible existence of trends (increase or decrease). Biomass burning can to influence the cloudiness and the rainfall, because it generates aerosols that act as cloud condensation nuclei (CCN). The time series of both cities maintained a similar pattern in the behavior and disruptions that revealed the existence of three distinct periods that can be related to burnings that occur in some Brazilian states. The first period is from the beginning of the series (1971 in Botucatu and 1980 in Piracicaba) to 1983, second period is from 1984 to 2008 and third period is from 2009 to 2012 or 2013. In the second period there was a tendency of reduction in the annual volume of rainfall. The occurrence of the three distinct periods are related to land use change in São Paulo State, to expansion of the agricultural frontier in the northern and middle-western Brazil and to increase in the practice of biomass burning.
Influence of burnings in the behaviour of rainfalls in the cities of Botucatu and Piracicaba, São Paulo state
Keywords: Aerosols; Climate change; Linear regression; Trend test